When less is more: the effects of prematurity on maternal attentional scaffolding and infant executive functioning - Ong, Jing Ting (Nanyang Technological University, 2024)
Premature birth poses a neurobiological risk for poorer subsequent cognitive outcomes and heterogeneous developmental trajectories for executive functioning. Socio-environmental protective factors that may attenuate risks of negative outcomes include parental scaffolding. However, it is not well-understood how attentional scaffolding in particular influences infant executive function as well as how infant prematurity modulates its effects. This study aimed to investigate how the relation between maternal attentional scaffolding and infant executive function is influenced by prematurity. It was hypothesised that more frequent effective attentional scaffolding would be associated with better executive function, and that this effect would vary with infants’ degree of prematurity. Mother-infant dyads (N = 38) consisting of 12- and 18-month-old term and preterm infants had undergone the A-not-B task. Infant executive function was mainly inferred from their reaction time while prematurity was proxied by their gestational ages. Maternal attention scaffolding was measured across 5 modalities: gaze, gaze-following, vocalisation, reach, and smile. Unexpectedly, fewer total effective attentional scaffolding was associated with shorter reaction times and higher accuracy, and it influenced both term and preterm infants’ performance to similar extents. However, fewer effective vocalisations in particular benefitted term infants more than preterm infants. Altogether, the results imply that the quality of attentional scaffolding may matter more than its quantity, highlighting the importance of contingent scaffolding. It may also be particularly important for mothers of preterm infants to provide contingent vocalisations to help scaffold their infants’ attention.